Analisis Nilai Kepadatan dan CBR Pada Gradasi Batas Atas, Median, dan Bawah Berdasarkan Rumus Cooper - Mahmudi, Imam, Ir. Agus Riyanto MT, Ir. Sri Sunarjono ST., MT., PhD (2016)
Highway is an infrastructure that is essential to people's lives, because it can affect the economy of a region. The problem of damage that occur each year and rising material prices pushing for road pavement recycling. RAP (Reclaimed Asphalt Pavement) is the result of the processing of pavement that still contain bitumen. RAP is one alternative that can be used. The purpose of this study to investigate the density and carrying capacity of the RAP has been graded with formula Cooper, then compare it with original RAP with cold mixing methods. Research method using a laboratory test from value of density and CBR. The materials used are original RAP without extraction and without the addition of new aggregate. In this research, experiment is used abrasion testing, extraction, density, moisture content, density and CBR. For density testing uses a standard Proctor and CBR tests without submergence (Unsoaked CBR). Number of samples that will be made in this research is 28 samples. This research was conducted at the Laboratory of Civil Engineering University of Muhammadiyah Surakarta. On research conducted shows results RAP that have been engineered with formula Cooper has better density values than original RAP. Maximum density values obtained 1.733 g / cm3, with the optimum moisture content of 7.8%. While original RAP is 1.55 g / cm3 with optimum moisture content 3.07%. This shows that RAP has been Graded with formula Cooper has better density values. On testing CBR, RAP engineered carrying capacity is also higher at 56.67%. Original RAP value amounted 27.67%.